THE RELATIONSHIP BETWEEN IRON TABLET COMPLIANCE AND HEALTHY DIETARY PATTERNS AND ANEMIA STATUS AMONG FEMALE ADOLESCENTS - Umi Nur Fajri; Dian Nirmala Sari; Lukman Hakim (Siklus : Journal Research Midwifery Politeknik Tegal, 2026)
The adolescent phase is nutritionally vulnerable phase because it requires more energy and nutrients for growth and development. Unbalanced nutrient consumption can lead to nutritional deficiencies. Adolescent girls with irregular eating patterns, having food restrictions, often buying snacks because they follow friends, often skipping breakfast, eating fast food, and junk food can cause anemia. Consumption habits that inhibit iron absorption will affect hemoglobin levels. Efforts to prevent anemia in adolescent girls include having a healthy lifestyle and providing iron tablet supplements taken regularly. The purpose of this study was to determine the relationship between adherence to iron tablet consumption and a healthy diet with anemia status in adolescent girls. The method used in this study was analytical research with a cross-sectional approach. The sample consisted of 30 female adolescents at SMPN 1 Banjarmangu. The sampling technique used was cluster sampling. The statistical test used was correlation with chi-square. The results showed a relationship between adherence to iron tablet consumption and anemia status (p-value 0.00), and there was no relationship between a healthy diet and anemia status (p-value 0.279).